The Influence of Corporate Governance Quality on Company Financial Performance with Capital Structure as a Moderating Variable in the Transportation & Logistics Sector on the Indonesian Stock Exchange - Putri, Juriani; Patrisia, Dina (Financial Management Studies, 2024)
This research aims to examine the influence of corporate governance quality on company performance with capital structure as a moderating variable. The population in this study were 36 transportation & logistics sector companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling method is proportional sampling, so that 26 sample companies were obtained with 96 observations. The type of data used is secondary data obtained from the Indonesian Stock Exchange website, namelywww.idx.co.idand sample company websites. The data analysis method uses Moderated Regression Analysis (MRA) using a programIBM SPSS Statistics 25. The research results show that (1) the quality of corporate governance (CGI) has an insignificant negative effect on company performance (ROA) (2) capital structure (DER) is able to moderate the relationship between the quality of corporate governance (CGI) and company performance